Anti-EGFR Binding Nanobody Delivery System to Improve the Diagnosis and Treatment of Solid Tumours - Wang, Long; Zhang, Gengyuan; Qin, Long; Ye, Huili; Wang, Yan; Long, Bo; Jiao, Zuoyi (Recent Patents on Anti-Cancer Drug Discovery, 2020)
Background: Epidermal Growth Factor Receptor (EGFR) and members of its homologous protein family mediate transmembrane signal transduction by binding to a specific ligand, which leads to regulated cell growth, differentiation, proliferation and metastasis. With the development and application of Genetically Engineered Antibodies (GEAs), Nanobodies (Nbs) constitute a new research hot spot in many diseases. A Nb is characterized by its low molecular weight, deep tissue penetration, good solubility and high antigen-binding affinity, the anti-EGFR Nbs are of significance for the diagnosis and treatment of EGFR-positive tumours. Objective: This review aims to provide a comprehensive overview of the information about the molecular structure of EGFR and its transmembrane signal transduction mechanism, and discuss the anti-EGFR-Nbs influence on the diagnosis and treatment of solid tumours. Methods: Data were obtained from PubMed, Embase and Web of Science. All patents are searched from the following websites: the World Intellectual Property Organization (WIPO®), the United States Patent Trademark Office (USPTO®) and Google Patents. Results: EGFR is a key target for regulating transmembrane signaling. The anti-EGFR-Nbs for targeted drugs could effectively improve the diagnosis and treatment of solid tumours. Conclusion: EGFR plays a role in transmembrane signal transduction. The Nbs, especially anti- EGFR-Nbs, have shown effectiveness in the diagnosis and treatment of solid tumours. How to increase the affinity of Nb and reduce its immunogenicity remain a great challenge.
Keywords: Diagnosis and treatment